Endocytic trafficking induces lateral root founder cell specification in Arabidopsis thaliana in a process distinct from the auxin-induced pathway - Morales-Herrera, Stefanía; Rubilar-Hernández, Carlos; Pérez-Henríquez, Patricio; Norambuena, Lorena (Frontiers in Plant Science, 2023)
Plants can modify their body structure, such as their root architecture, post-embryonically. For example, Arabidopsis thaliana can develop lateral roots as part of an endogenous program or in response to biotic and abiotic stimuli. Root pericycle cells are specified to become lateral root founder cells, initiating lateral root organogenesis. We used the endocytic trafficking inducer Sortin2 to examine the role of endomembrane trafficking in lateral root founder cell specification. Our results indicate that Sortin2 stimulation turns on a de novo program of lateral root primordium formation that is distinct from the endogenous program driven by auxin. In this distinctive mechanism, extracellular calcium uptake and endocytic trafficking toward the vacuole are required for lateral root founder cell specification upstream of the auxin module led by AUX/IAA28. The auxin-dependent TIR1/AFB F-boxes and auxin polar transport are dispensable for the endocytic trafficking–dependent lateral root founder cell specification; however, a different set of F-box proteins and a functional SCF complex are required. The endocytic trafficking could constitute a convenient strategy for organogenesis in response to environmental conditions.